Các hợp chất phenolic glycoside Phân lập từ cây đại cà dược (Brugmansia suaveolens) - Mai, Nguyễn Thị; Cúc, Nguyễn Thị; Yến, Phạm Hải; Tài, Bùi Hữu (Vietnam Journal of Chemistry, 2016)
Six phenolic glycosides, kaempferol 3-O-a-L-arabinopyranoside 7-O-a-L-rhamnopyranoside (1), kaempferol 3-O-b-D-glucopyranoside 7-O-a-L-rhamnopyranoside (2), kaempferol 3-O-β-D-glucopyranosyl-(1→2)-β-D-glucopyranoside 7-O-α-L-rhamnopyranoside (3), benzyl-a-L-arabinopyranosyl-(l®6)-b-D-glucopyranoside (4), 2,6-dimethoxy-4-hydroxyphenol 1-O-b-D-xylopyranosyl-(1→6)-b-D-glucopyranoside (5), and 2,6-dimethoxy-4-hydroxyphenol 1-O-β-D-glucopyranoside (6) were isolated from the methanol extract of Brugmansia suaveolens. Their chemical structures were characterized by 1D-, 2D-NMR, ESI-MS spectra, and as well as in comparison with those reported in the literature. This is the first report of these compounds from B. suaveolens